Cutoffs on severity metrics for minimal manifestations or better status in patients with generalized myasthenia gravis - Watanabe, Genya; Takai, Yoshiki; Nagane, Yuriko; Kubota, Tomoya; Yasuda, Manato; Akamine, Hiroyuki; Onishi, Yosuke; Uzawa, Akiyuki; Kawaguchi, Naoki; Masuda, Masayuki; Konno, Shingo; Amino, Itaru; et al. (Frontiers in Immunology, 2024)
International consensus guidance and Japanese clinical guidelines for myasthenia gravis (MG) recommend achieving minimal manifestations or better status (MM-or-better) as the severity component of the treatment goal. However, the subjective nature of determining MM can result in ambiguity regarding this category in clinical practice and clinical trials. This study analyzed severity metrics in a large number of MG patients to propose criteria for MM-or-better. We utilized data obtained from 3800 MG patients who participated in nationwide cross-sectional surveys in Japan. Among these, 2784 patients with generalized MG were divided into two groups based on MG Foundation of America postintervention status: MM-or-better status (n = 1432); and improved-or-worse (I-or-worse) status (n = 1352). We compared severity metrics (MG-activities of daily living scale [MG-ADL], quantitative MG score [QMG], and MG composite scale [MGC]) between groups and calculated cutoff values to separate the two groups. Using these cutoffs, patients subjectively assigned as MM-or-better were classified into strict MM-or-better (below a cutoff) or optimistic MM-or-better (above a cutoff) groups, and clinical characteristics were then compared. Cutoff values for strict MM-or-better were MG-ADL ≤2, QMG ≤7, and MGC ≤4 (sensitivity 82.0%, 88.7%, and 87.4%; specificity 85.0%, 70.0%, and 77.9%; and accuracy 91.2%, 88.7%, and 90.7%, respectively). Mean values of the revised 15-item MG quality of life scale were significantly lower in the strict MM-or-better group than in the optimistic MM-or-better group. Quantitative criteria for MM-or-better appear likely to be useful in the context of rigorous clinical trials and also as reference information in clinical settings.